Longitudinal MRI reveals impaired cortical thinning in children and adolescents prenatally exposed to alcohol - Treit, Sarah (Hum Brain Mapp, 2014)
Brain imaging studies suggest that cortical thickness decreases during childhood and adolescence, in concert with underlying structural and synaptic changes required for cognitive maturation and regional specialization of function. Abnormalities of this protracted developmental process may provide key insights into the cognitive and behavioral deficits that emerge in individuals with fetal alcohol spectrum disorders (FASD). Several studies have demonstrated cortical thickness differences in children and adolescents who were prenatally exposed to alcohol, though all have been cross sectional, limiting conclusions about cortical development with age. In this study, we analyze serially collected T (1)‐weighted MRI from 11 children with FASD and 21 controls, scanned twice each ∼2 to 4 years apart. Mixed‐models analysis of cortical thickness measurements revealed age‐by‐group interactions in cortical thinning, with FASD participants undergoing less developmental thinning than controls across many regions of the cortex, particularly in medial frontal and parietal areas. These results provide further longitudinal evidence in humans that prenatal alcohol exposure is associated with altered patterns of brain development that persist during childhood and adolescence. Hum Brain Mapp 35:4892–4903, 2014. © 2014 Wiley Periodicals, Inc.